An Overview of Biocement Production from Microalgae - Dessy Ariyanti; Noer Abyor Handayani; Hadi Hadiyanto (International Journal of Science and Engineering, 2011)
The invention of microorganism’s involvement in carbonate precipitation, has lead the exploration of this process in the field of construction engineering. Biocement is a product innovation from developing bioprocess technology called biocementation. Biocement refers to CaCO3 deposit that formed due to microorganism activity in the system rich of calcium ion. The primary role of microorganism in carbonate precipitation is mainly due to their ability to create an alkaline environment (high pH and DIC increase) through their various physiological activities. Three main groups of microorganism that can induce the carbonate precipitation: (i) photosynthetic microorganism such as cyanobacteria and microalgae; (ii) sulphate reducing bacteria; and (iii) some species of microorganism involved in nitrogen cycle. Microalgae are photosynthetic microorganism and utilize urea using urease or urea amidolyase enzyme, based on that it is possible to use microalgae as media to produce biocement through biocementation. This paper overviews biocement in general, biocementation, type of microorganism and their pathways in inducing carbonate precipitation and the prospect of microalgae to be used in biocement production.  Keywords— Biocement, Biocementation, Microalgae, CaCO3 precipitation